Analysis of The Influence Between Mining, Agriculture and Processed Product Exports on Indonesia's Sales Development in International Trade in the Time Frame 2019-2022 - Amalia Renata Anggraeni; Sigit Puji Winarko; Erna Puspita (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Exports are one of the international trade activities that provide benefits to Indonesia, including capital transactions, employment, and foreign exchange reserves. There are 2 types of exports, namely oil and gas and non-oil and gas exports. The value of non-oil and gas exports tends to be higher than oil and gas exports. So this research focuses on three non-oil and gas sectors, which consist of mining, agriculture, and processing industry (processed products). The purpose of this study is to determine the effect of mining, agriculture, and processed product exports on Indonesia's sales in international trade in the 2019-2022 timeframe. This research uses a quantitative approach, and a multiple linear regression analysis model with the IBM SPSS 22 application. The research data comes from the Central Bureau of Statistics, the Ministry of Trade, and related agencies. The variables used include 3 independent variables and 1 dependent variable. The independent variables are mining exports (X1) with the commodities used are coal, copper, lignite, iron and steel, agricultural exports (X2), and exports of processed products (X3), and Indonesia's sales as the dependent variable (Y). Based on the results of the study, partially shows that mining exports, and processed products have a significant positive effect on Indonesian sales. While agricultural exports (X2) have no effect on Indonesian sales (Y).